Perancangan Sistem Informasi E-Surat pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Ketenagakerjaan Berbasis Web - Giben Frautama Manik; Marlyna Infryanty Hutapea; Gortap Lumbantoruan (Universitas Methodist Indonesia, 2024)
This research aims to design a web-based e-letter information system for the One-Stop Investment and Integrated Service Agency and Manpower (DPMPTSPK). The system is designed to facilitate the management of incoming and outgoing letters, as well as to improve efficiency in office administration. The issues faced by the related agency include a manual letter archiving process that is slow and prone to human error, which hinders service delivery. This research employs a system development method using the System Development Life Cycle (SDLC) approach, which includes stages of needs analysis, system design, implementation, and testing. The technology used is web-based programming, with PHP as the programming language and MySQL as the database for data management. This system enables integration of electronic letters, status tracking of letters, and easy archive searches. The results of the research indicate that the designed e-letter system is capable of accelerating the letter management process, reducing the risk of document loss, and enhancing transparency and accountability within the organization. With this system in place, it is hoped that DPMPTSPK can provide more effective and efficient services to the public.